Practicality of multilayer round window reinforcement in the surgical management of superior semicircular canal dehiscence syndrome: a case report of long-term follow-up - Sawada, Masafumi; Matsuda, Han; Tanzawa, Yasuhiko; Sakamoto, Kei; Kudo, Hiroe; Nakashima, Masato; Ikezono, Tetsuo (Frontiers in Neurology, 2024)
Several surgical techniques have been documented for approaching and repairing superior semicircular canal dehiscence syndrome (SCDS). These techniques encompass the trans-middle cranial fossa, transmastoid, endoscopic approaches, and round window reinforcement (RWR). RWR entails the placement of connective tissue with or without cartilage and around the round window niche, restricting the round window's movement to minimize the 3rd window effect and restore the bony labyrinth closer to its normal state. We employed the multilayer RWR technique, resulting in significant postoperative improvement and long-lasting effects for 3.7 years in 2 cases. Here, we present the clinical findings, surgical procedures, and the effectiveness of multilayer RWR. This technique can be the initial choice for surgical treatments of SCDS due to its high effectiveness, longer-lasting effect, and minimal risk of surgical complications.